Succinic Semialdehyde Dehydrogenase Deficiency in a Chinese Boy - Tay, C.G.; Ariffin, H.; Yap, S.; Rahmat, K.; Sthaneshwar, P.; Ong, L.C. (SAGE Publications (UK and US), 2015)
Succinic semialdehyde dehydrogenase deficiency is a rare autosomal recessive disorder affecting catabolism of the neurotransmitter gamma-aminobutyric acid (GABA), with a wide range of clinical phenotype. We report a Malaysian Chinese boy with a severe early onset phenotype due to a previously unreported mutation. Urine organic acid chromatogram revealed elevated 4-hydroxybutyric acid. Magnetic resonance imaging (MRI) of the brain demonstrated cerebral atrophy with atypical putaminal involvement. Molecular genetic analysis showed a novel homozygous 3-bp deletion at the ALDH5A1 gene c.1501-1503del (p.Glu501del). Both parents were confirmed to be heterozygotes for the p.Glu501del mutation. The clinical course was complicated by the development of subdural hemorrhage probably as a result of rocking the child to sleep for erratic sleep-wake cycles. This case illustrates the need to recognize that trivial or unintentional shaking of such children, especially in the presence of cerebral atrophy, can lead to subdural hemorrhage.